Using semantic mapping strategy to improve students speaking skill - Alfiani, Syafira (2020)
The eighth graders of SMPN 1 Kalianget, Madura had problem in speaking. The result of preliminary study showed that the students had difficulty in speaking due to lack of English vocabulary. Thus, semantic-mapping strategy (henceforward, SMS) was chosen to improve the students' English vocabulary, hence their speaking skill improved. The design of this study is Classroom Action Research (CAR) with three instruments, i.e. speaking test, speaking scoring rubric and questionnaire. The research was done in two cycles consisting of two meetings in each cycle. The criteria of success in this research is 75% of students show a gain of ≥ 8 points and 85% of students show positive response towards the implementation of SMS. Based on the findings, it can be concluded that SMS helped to improve the students' vocabulary and enabled them to speak English better